Strategi Dalam Pengembangan SDM Di Era Global (Studi Kasus Pada Rumah Makan Ayam Goreng Nelongso Bangkalan) - Nia Aisyah; Putri Handayani; Moh. Zidan Rikza; Iriani Ismail (Pusat Riset dan Inovasi Nasional, 2023)
Developments in this global era bring many changes that require a company to have human resources that can compete in current developments. This research aims to determine the existing HR development strategy at the Nelongso Bangkalan Fried Chicken restaurant. The method used in this research is qualitative with data collection techniques in the form of observation, interviews and documentation. The sample in this study used purposive sampling technique. Managers and staff employees were the samples (informants) in this research. The technique used to test the validity of the data is using the triangulation technique. The results of this research show that implementing appropriate HR development strategies can increase employee productivity and company competitiveness in facing the global era..